Adaptation And Selection of Early Maturing And High-Yielding Production of Some Exotic Rice Genotypes Under Egyptian Conditions - El-Badawy, O.A.; Soltan, S.A.; Bleih, M.E.; Anis, G.B.; Taha, A.S.; EL -Namaky, R.A. (Egyptian Knowledge Bank, 2024)
successive seasons during 2020 and 2021 at the Experimental Farm of Sakha Agricultural Research station, Sakha, Kafr El-Sheikh, Egypt, for identify and select the desirable early and high grain yield promising genotype under Egyptian conditions. Analysis of variance showed highly and significant differences among rice genotypes for all the studied traits. Grain yield of most rice genotypes was higher than check cultivars, the desirable genotypes, AFR0280, AFR278-2-2 and AFR278-8 recorded highest grain yield, 14.26, 14.03 and 14.00 (t/ha), respectively during seasons, genotypic and phenotypic coefficient of variation (PCV) were observed greater than environmental coefficient of variation as well as, high values of heritability (>85%) was observed for all studied characters, indicated to superior the genetic control for the expression to the studied characters and could be suggest that, these traits can be enhance through direct selection. Grain yield was positively and strongly correlated with each of plant he